Chapter La voce delle scuole - Grilli, Antonella (Strumenti per la didattica e la ricerca, 2022)
Documentation of the experiences of the experimental project Direct Digital Integrated Internship, partly presented in the accompanying conferences, in the academic year 2020-2021, in which headteachers, school tutors and University Tutors of the Tuscany region and the students of the Course of Studies in Primary Education at the University of Florence.